2020
DOI: 10.1080/02670844.2020.1763765
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and tribological behaviour of titanium boride coatings processed by thermochemicals treatments

Abstract: The present work aims to study the mechanical and tribological properties of titanium boride layer processed by a thermochemical boriding treatment, which was carried out in a salt bath consisting of 70% borax and 30% silicon carbide. The boriding temperatures were 850°C, 950°C and 1000°C with holding times of 2, 4, 6 and 8 h. The analysis by optical and scanning electron microscopy and X-ray diffraction method confirmed the formation of a single-phase layer of titanium diboride (TiB 2 ) in the substrate surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…However, the composition of this surface layer varies; for example, in nitriding, the surface layer is made up of TiN. The process involves submerging the metal into a molten salt bath at temperatures between 950 and 1050 • C for 2-8 h before being quenched in water [96]. These baths create diffusion zones of ~5-7 μm thickness rich in carbon, nitrogen, and/or oxygen [97].…”
Section: Thermochemical Salt Bath Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the composition of this surface layer varies; for example, in nitriding, the surface layer is made up of TiN. The process involves submerging the metal into a molten salt bath at temperatures between 950 and 1050 • C for 2-8 h before being quenched in water [96]. These baths create diffusion zones of ~5-7 μm thickness rich in carbon, nitrogen, and/or oxygen [97].…”
Section: Thermochemical Salt Bath Treatmentsmentioning
confidence: 99%
“…These baths create diffusion zones of ~5-7 μm thickness rich in carbon, nitrogen, and/or oxygen [97]. The single-phase nature of these surface layers typically offers increased hardness and wear resistance which contributes to an increased corrosion resistance [96]. However, the concentration of oxygen in the salt bath must be strictly controlled to prevent excess Ti-6Al-4V Increasing rotational speed of tool increased residual stress in workpiece after treatmentincrease of 100 RPM increased residual stress by 120 MPa.…”
Section: Thermochemical Salt Bath Treatmentsmentioning
confidence: 99%
“…[84][85][86][87] and spraying techniques (thermal spraying, plasma spraying, etc.) [88][89][90] were suggested in the literature as ways to deposit biocompatible HA coatings on the implant surface. Electric discharge machining (EDM) process is now widely recognized as being essential for creating nanostructured biocompatible recast layer on the implant surface and for having a positive effect on the biological attachment of human osteoblastic cells [91,92].…”
Section: Biomaterials Properties and Surface Modificationmentioning
confidence: 99%
“…Exploring further, boriding process can increase the surface hardness of the titanium alloy by forming a superhard layer of TiB 2 /TiB (Zheng et al , 2020). Khater et al (2021) found that the thickness of the boride layer obtained at 1000°C for 8 h was 50 μm, and the surface hardness and the elastic modulus of the Ti6Al4V substrate were greatly increased by the formation of TiB 2 layer. Zhu et al (2021) fabricated a dual titanium boride layer using solid-state boriding with the rare earth elements; the test results showed that the improvement of tribological performance of boride layer was dominated by the hard TiB 2 layer and soft shear accommodating TiB layer.…”
Section: Introductionmentioning
confidence: 97%